Identities in an era of globalization and multiculturalism : Latin America in the Jewish world - Bokser de Liwerant, Judit (Jewish identities in a changing world ;, 2008)
This volume addresses key conceptual issues and case studies dealing with contemporary Jewish identities amidst globalization processes, with special emphasis on Latin American socio-political, communal, and cultural milieu. The book brings together a variety of disciplinary and theoretical approaches that range from political science to sociology and from art and literature to demography in order to offer the reader a multidimensional and multifocal analysis of the diverse constitutional elements of the Jewish experience. Using as its point of departure the wide horizon of historical trajector.